2016
DOI: 10.5539/ijc.v8n1p178
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Harmful Substances and Health Risk Assessment of Mercury and Arsenic in Cosmetic Brands in Nigeria

Abstract: Forty two different cosmetic samples consisting of 16 facial cosmetics, 6 soaps, 1 shower gel, 12 emulsions, 2 underarm cosmetics, 3 nail cosmetics and 2 perfumes were purchased from department stores and cosmetic shops within Onitsha Main Market and Eke-Awka in Anambra, Nigeria. Seven of these cosmetic (16.67%) were locally manufactured in Nigeria while thirty five (83.33%) were imported into Nigeria. The cosmetics were ashed before digestion and filtration. The filtrates were assayed for mercury and arsenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 10 publications
3
9
1
Order By: Relevance
“…The results of the study were found consistent with the findings of Nduka et al The aim of the study was to evaluate the use of harmful substances used in cosmetic brands in Nigeria and assess their side effects. The study found the traces of arsenic, mercury, and other harmful chemicals in the cosmetics among 42 cosmetic sample out of which seven were manufactured in Nigeria and thirty‐five of them were imported to Nigeria.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The results of the study were found consistent with the findings of Nduka et al The aim of the study was to evaluate the use of harmful substances used in cosmetic brands in Nigeria and assess their side effects. The study found the traces of arsenic, mercury, and other harmful chemicals in the cosmetics among 42 cosmetic sample out of which seven were manufactured in Nigeria and thirty‐five of them were imported to Nigeria.…”
Section: Discussionsupporting
confidence: 84%
“…The results of the study were found consistent with the findings of Nduka et al8 The aim of the study was to evaluate the use of harmful substances used in cosmetic brands in Nigeria and assess their side effects. The study found the traces of arsenic, mercury, Distribution of present age and age of first usage of cosmetics by students involved in this study…”
supporting
confidence: 87%
“…Hence, it implies that higher population of Nigerians may not be aware of twin health hazards that may be caused by consumption of local analgesic drugs and the constituent heavy metal impurity. This is more worrisome by the non-existence of functional data on possible medical diagnostics result of ailments from painkiller drugs, heavy metal and other chemical constituents [ 1 ]. Rapidly growing and unregulated informal sector of the economy consisting of peasants, micro scale and several uncategorized occupation [ 2 ] is a sector of unspecialized skills where most jobs are at crude level and labour intensive, its intensity may result to body stress as most work place activities are still done manually against automation.…”
Section: Introductionmentioning
confidence: 99%
“…Nduka et al [35,36] assessed the cancer and no cancer risk of heavy metals, steroids, hydroquinone, nitrosamines and nitrites in 42 cosmetic brands purchased from cosmetic shops in Southeastern Nigeria through dermal exposure pathway; the total cancer risk value for both the cosmetic products manufactured in Nigeria and the cosmetic products manufactured outside Nigeria was less than the regulatory purpose acceptable or tolerable risk level of 10 −6 to 10 −4 set by USEPA [37]. This implies that the low levels of these carcinogenic elements to which users of these cosmetics are continually exposed to through the dermal exposure pathway alone over their lifetime are unlikely to pose a non-cancer and cancer risk.…”
Section: Bibliographies That Prove Cosmetic Brands Are In Continuous mentioning
confidence: 99%
“…It further stated that mercury salts inhibit the formation of melanin, resulting in lighter skin tone. The review showed countries of greatest cosmetic use in Africa, Mali, Senegal, South Africa, Togo and Nigeria in order of increasing usage by women as 25,27,35,59 and 77% are reported to use skin lightening products on a regular basis. Close to 40% of women surveyed in China, Malaysia, the Philippines and Republic of Korea in the year 2004 were reported to have used skin lighteners, while in India, 61% of the dermatological market were made of skin lightening products.…”
Section: Bibliographies That Prove Cosmetic Brands Are In Continuous mentioning
confidence: 99%